2022
DOI: 10.1016/j.jhepr.2022.100430
|View full text |Cite
|
Sign up to set email alerts
|

Malignant transformation of hepatocellular adenoma

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…A recent study of malignancy in HCA cases reported a surprisingly high frequency of malignant transformation of IHCA without β‐catenin mutation 66 . However, these findings could not be replicated by another recent study 67 …”
Section: Hca Classificationmentioning
confidence: 79%
See 3 more Smart Citations
“…A recent study of malignancy in HCA cases reported a surprisingly high frequency of malignant transformation of IHCA without β‐catenin mutation 66 . However, these findings could not be replicated by another recent study 67 …”
Section: Hca Classificationmentioning
confidence: 79%
“…However, the evaluation is biased, owing to the inclusion of only surgical samples. In addition, the presence of an HCA in an HCC, or a history of incomplete resection of an HCA, is a prerequisite for the diagnosis of HCA‐derived HCC; therefore, the precise frequency of pre‐existing HCA behind a fully developed HCC in a non‐cirrhotic liver is unknown 67,81 …”
Section: Hca Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…We are honored to receive the pertinent and relevant comments of Céline Julien et al. , 1 and we enjoyed reading about the Bordeaux group’s experience with malignant transformation of hepatocellular adenoma (HCA). We are pleased to address the issues they raised regarding our study, which concerns a matched case-control study comparing the long-term outcome after liver resection for HCA with malignant transformation (MT-HCA) to hepatocellular carcinoma (HCC) developed on normal liver-parenchyma.…”
mentioning
confidence: 99%